PENGUNGKAPAN PAJAK DI INDONESIA: SEBUAH CONTENT ANALYSIS - Dian Purnama Sari; Tigor Tambunan; Natalia Kristina; Joshua Leong; Eirene Puspita Wardoyo (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
Many countries are starting to require tax disclosure. In Indonesia, the Mandatory Disclosure Rule (MDR) has been announced but has never been implemented. Tax disclosure is expected to be an alternative change to the Mandatory Disclosure Rule (MDR). The purpose of this study is to analyze tax disclosures made by companies in Indonesia. This research was conducted using the content analysis method to classify and measure each of Mgammal's (2019) measurement items more accurately. The results showed that 12 items were fully represented by all company samples, 13 items were presented as company samples and 6 measurement items were not presented at all by company samples. It is hoped that the implementation of tax disclosure measurements carried out in this research can become a basis for compiling relevant tax disclosure items in Indonesia.